Efficient approach for iris recognition. Issue 7 (October 2016) - Hamouchene, Izem; Aouat, Saliha
Abstract Iris texture is a natural password that has great advantages such as variability, stability, unique features for each person, and its importance in the security field. This makes an iris recognition system upper of other biometric methods used for human identification. Recent science is interested to develop intelligent systems able to identify persons based on the texture of their iris. We proposed a new feature extraction method based on local and directional texture information. The proposed feature extraction method gets both local and global relevant information and faster than commonly used method. In the experimental parts, our system is compared to other famous and recent iris recognition systems using CASIA iris dataset. Experiments demonstrate that the proposed system gives better recognition rate (99.96 %) compared to other systems.